2012
DOI: 10.1371/journal.pone.0029124
|View full text |Cite
|
Sign up to set email alerts
|

HGF-Induced PKCζ Activation Increases Functional CXCR4 Expression in Human Breast Cancer Cells

Abstract: The chemokine receptor CXCR4 and its ligand CXCL12 have been shown to mediate the metastasis of many malignant tumors including breast carcinoma. Interaction between hepatocyte growth factor (HGF) and the Met receptor tyrosine kinase mediates development and progression of cancers. HGF is able to induce CXCR4 expression and contributes to tumor cell invasiveness in breast carcinoma. However, the mechanism of the CXCR4 expression modulated by c-Met-HGF axis to enhance the metastatic behavior of breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…PKCζ has been implicated in the invasive phenotype of human cancers [36], [37], [38]. RNAi-mediated, specific inhibition of PKCζ reduces breast cancer and glioblastoma cell invasion in vitro [37], [38] and reduces prostate cancer cell invasion in vitro and in vivo [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKCζ has been implicated in the invasive phenotype of human cancers [36], [37], [38]. RNAi-mediated, specific inhibition of PKCζ reduces breast cancer and glioblastoma cell invasion in vitro [37], [38] and reduces prostate cancer cell invasion in vitro and in vivo [36].…”
Section: Discussionmentioning
confidence: 99%
“…RNAi-mediated, specific inhibition of PKCζ reduces breast cancer and glioblastoma cell invasion in vitro [37], [38] and reduces prostate cancer cell invasion in vitro and in vivo [36]. Interestingly, each of these reports attributes PKCζ to a distinct invasive signaling pathway, suggesting a broad role for PKCζ in cancer cell invasion [36], [37], [38]. Consistent with the phenotype observed in other cancers, we determined that inhibition of PKCζ expression not only inhibited the transformed growth of pancreatic cancer cells, but also repressed their invasive potential in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Such an endocrine pathway is required for moving cells to determine the homing sites. Of note, HGF enhances CXCR4 expression by cancer cells [51]. Furthermore, HGF enhances the ability of SDF1 to promote cancer invasion [52].…”
Section: Hgf-mediated Cancer Metastasismentioning
confidence: 99%
“…Phillips et al[28] indicated that epidermal growth factor and hypoxia promoted CXCR4 expression via PI3K/AKT/mTOR pathway in non-small cell lung cancer. Huang et al[29] also reported that the PI3K/AKT pathway was involved in CXCR4 expression and the hepatocyte growth factor-induced activation of protein kinase C-ζ in human breast cancer cells. Moreover, Dubrovska et al[30] demonstrated the direct regulation of CXCR4 expression by the PI3K pathway and thus implied a mutually positive regulatory feedback loop between the PI3K/AKT and CXCR4/CXCL12 signaling pathways, which are both important for cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%